Business reinvention for ecosystem value, flexibility and empowerment emerging research and opportunities - Yuan, Soe-Tsyr (Advances in business strategy and competitive advantage., 2020)
"This book provides a business reinvent methodology that systematically choreographs the right components for the reinvention together and the strategic assessments about how to undertake the change"--